Profitability of the Korean banking sector: panel evidence on bank-specific and macroeconomic determinants - Sufian, Fadzlan (Feng Chia University, 2011)
The paper analyzes the profitability of banks in Korea, while controlling for a wide array of bank specific and macroeconomic determinants. We find that Korean banks with lower liquidity levels tend to exhibit higher profitability. Furthermore, higher diversification regarding banks’ income sources towards derivative instruments and other fee-based activities shows a positive effect. The impacts of credit risk and overhead costs are always negative whether we control for the macroeconomic and financial conditions or not. Business cycle effects, particularly inflation, display a substantial pro-cyclical impact on bank profitability. The industry concentration of the national banking system positively and significantly affects bank performance. The impact of the Asian financial crisis is negative, while Korean banks have been relatively more profitable during the pre-crisis compared to the post-crisis period.